2020
DOI: 10.1002/ehf2.12923
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signatures of cardiac remodelling and heart failure risk in the community

Abstract: Aims Heart failure (HF) is associated with several metabolic changes, but it is unknown whether distinct components of the circulating metabolome may be related to cardiac structure and function, and with incident HF in the community. Methods and results We assayed 217 circulating metabolites in 2336 Framingham Study participants (mean age 55 ± 10 years, 53% women) without HF at baseline. We used linear and Cox regression to relate concentrations of metabolites to left ventricular (LV) diastolic dimension, LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
3
21
0
1
Order By: Relevance
“…Glutamine was inversely associated with heart rate ( β = −13, P = 1 × 10 −4 ). As previously reported for prevalent association, 5 we also found asparagine to be associated with LV internal dimension.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Glutamine was inversely associated with heart rate ( β = −13, P = 1 × 10 −4 ). As previously reported for prevalent association, 5 we also found asparagine to be associated with LV internal dimension.…”
Section: Resultssupporting
confidence: 90%
“…We confirm several previous metabolite associations with cardiac remodelling parameters and heart failure. Increased α‐ketoglutarate correlated with increased LV wall thickness, while increased asparagine demonstrated an association with increased LV diastolic dimension 5,13 . Higher levels of ornithine, which has a role in the urea cycle, were associated with CHF 5 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sample selection and storage specifications were not consistently reported across the studies. In some cases, samples were stored for 15 years or more prior to analysis [6,11,12,54] in which degradation of some metabolites is possible. We are not aware of any of the studies from our review that reported on the measurement of preanalytical quality markers or adjusted for sample preanalytical confounders.…”
Section: Sample Selectionmentioning
confidence: 99%
“…В научной литературе появляется все больше работ, анализирующих ассоциацию метаболитов с параметрами ремоделирования миокарда и особенностями течения СН. Так, в ретроспективном исследовании данных метаболомного профиля 2 336 участников Фрамингемского исследования, период наблюдения за которыми составил в среднем 15,8 года, была продемонстрирована четкая связь трех метаболитов с параметрами ремоделирования ЛЖ: кинуренина, диацилглицерола и лейцина с конечным диастолическим размером ЛЖ [43]. В другом исследовании 74 пациентов с ишемической болезнью сердца обнаружена отрицательная корреляция уровня сфингозин-1-фосфата и сфингомиелина с величиной фракции выброса ЛЖ [44].…”
Section: метаболомикаunclassified